(3GdbQGUfI hGdbQT GdCHjV (B:s (3QhGjI ddTHGH (B/s - (3Rcj, YeGOs 1957- ((3dfOf (B:s (3OGQ QhGjI,s, 2000)
(3JJfGhd QhGjI (B((3GdbQGUfI hGdbQT GdCHjV(B) (3hGdJj bGe HJCdjagG (B((3YeGO Rcj(B) (3aj MhGdj (B(59) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbUU GdYQHjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3SHGb UjO GdbQT, Ccd GdbQT bHd Cf jCcdg, gLhe GdbQT GdZGVH, CKbd bQT aj GdYGde, bQUGf (B"(3ehOQf(B"(3, HGfJXGQ GdfLOI, hVGY GdCed GdCNjQ, NHQ YGLd, dZR GdbQGUfI, Edi ebOjTh, GdZehV jROGO, GdeaGLCI GdeKjQI, bfGI (B"(3GdeZGeQhf(B"s
(3hQO Ydi GdZdGa (B: (3QhGjI ddTHGf(B.s
(3ehLg ddTHGH(B.s
Keywords: (3GdbUU GdYQHjIs -- (3QhGjIs -- (3GdCQOfs -- (3bQf (B21s